A high-strength and high-toughness adhesive tape and its preparation process
By using modified carbon fiber and a PVC film layer with a specific formula in the insulating tape, the problem of insufficient tape strength and toughness is solved, and the preparation of high-strength and high-toughness tape is achieved, ensuring the mechanical properties and bonding effect of the tape.
Patent Information
- Application Number
- CN202311341973.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-10-17
AI Technical Summary
The existing insulating tape has insufficient mechanical properties, it is prone to stress damage or cracking, and has poor bonding effect, making it difficult to meet the needs of high strength and high toughness.
The combined structure of PVC film layer and glue layer is adopted, wherein the raw materials of the PVC film layer include PVC, calcium carbonate, modified carbon fiber, magnesium stearate, tributyl acetyl citrate, dioctyl phthalate and titanium dioxide powder. Through specific modified carbon fiber treatment and mixing processes, the binding force and distribution uniformity of carbon fibers and PVC are improved.
It significantly improves the strength and toughness of PVC film, has excellent mechanical properties, enhances the tensile strength and crack resistance of the tape, and ensures good bonding effect.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive tape materials, and in particular to a high-strength and high-toughness adhesive tape and a preparation process thereof. Background Art
[0002] Insulating tape refers specifically to the tape used by electricians to prevent leakage and act as an insulator. It is also called insulating tape or tape tape, which consists of a base tape layer and an adhesive layer. The base tape layer is generally made of cotton cloth, synthetic fiber fabric, and plastic film, and the adhesive layer is made of rubber and a compounding agent such as a tackifying resin, with good viscosity and excellent insulation performance. Insulating tape has good insulation pressure resistance, flame retardancy, and weather resistance, and is suitable for wire connection, electrical insulation protection, and other characteristics. PVC tape is a new type of material made with PVC film as the base tape layer. It has excellent electrical insulation, sealing, wear resistance, flame resistance, and acid and alkali chemical corrosion resistance, and is widely used in the packaging industry, construction industry, electronics industry, automobile and shipbuilding industry, and coal mining industry. Summary of the invention
[0003] To this end, the present invention provides a high-strength and high-tenacity adhesive tape and a preparation process thereof, comprising a PVC film layer and an adhesive layer, wherein the raw materials of the PVC film layer include PVC, calcium carbonate, modified carbon fiber, magnesium stearate, acetylcitrate tributyl, dioctyl phthalate and titanium dioxide powder, and the modification method of the modified carbon fiber is:
[0004] (1) preparing an ethanol solution of γ-aminopropyltriethoxysilane, immersing the carbon fiber in the ethanol solution of γ-aminopropyltriethoxysilane to form a mixed solution, the mixed solution is kept at a constant temperature of 50±3°C in a water bath, glacial acetic acid is added dropwise to adjust the pH of the mixed solution to 4-5, then the mixed solution is stirred at a constant temperature of 50±3°C for 30-50min, air-cooled to room temperature, solid-liquid separated, the solid phase is washed with ethanol for more than 3 times, dried, and the dried solid phase is immersed in ethanol again to form an alcohol solution, the alcohol solution is kept at a constant temperature of 70±3°C in a water bath, condensed and refluxed; stirring the alcohol solution, adding methyl methacrylate to the alcohol solution during the stirring process, stirring the alcohol solution for more than 10min after the addition is completed, and then adding dibenzoyl peroxide to the alcohol solution under stirring, continuing to stir the alcohol solution at a constant temperature of 70±3°C for more than 5h after the addition is completed, then air-cooled to room temperature, solid-liquid separated, the solid phase is washed with ethanol for more than 3 times, and dried at 60°C to obtain a primary modified product;
[0005] (2) preparing an acetone solution of benzophenone and an aqueous solution of 1-vinyl-2-pyrrolidone; dispersing the primary modified product in the acetone solution of benzophenone to form a dispersion, stirring the dispersion, adding the aqueous solution of 1-vinyl-2-pyrrolidone to the dispersion during the stirring process, stirring the dispersion for more than 20 minutes after the addition is completed, then pouring the dispersion into a glass dish, irradiating with an ultraviolet lamp for 10 to 15 minutes, then separating the solid and the liquid, washing the solid phase with ethanol and water twice each, and drying at 60° C. to obtain a secondary modified product;
[0006] (3) In a reactor under a nitrogen atmosphere, an N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride is prepared, and then the secondary modified product is added to the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride under nitrogen protection; after the addition is completed, the mixture is stirred for more than 10 minutes, and then acetic anhydride is added under stirring. After the addition is completed, the mixture is stirred for more than 5 minutes under nitrogen protection, and then the reactor is closed, and the temperature is kept constant at 60±2° C. in a water bath for more than 3 hours, and then the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with ethanol for more than 3 times, and then dried at 60° C. to obtain the modified carbon fiber.
[0007] Furthermore, the raw materials of each PVC film layer are calculated by weight as follows: 100 parts of PVC, 3 to 5 parts of calcium carbonate, 20 to 30 parts of modified carbon fiber, 5 to 8 parts of magnesium stearate, 4 to 10 parts of acetyl tributyl citrate, 1 to 4 parts of dioctyl phthalate, and 1 to 4 parts of titanium dioxide powder, and each solid component is a sieved powder passing through 500 mesh.
[0008] Furthermore, in the step (1), the concentration of γ-aminopropyltriethoxysilane in the ethanol solution of γ-aminopropyltriethoxysilane is 1 to 2 g / 100 mL, and the solvent is ethanol; the solid-liquid mass ratio of the carbon fiber immersed in the ethanol solution of γ-aminopropyltriethoxysilane is carbon fiber / ethanol solution of γ-aminopropyltriethoxysilane = 1:80.
[0009] Furthermore, in the step (1), the dried solid phase is immersed in ethanol again to form an alcohol solution with a solid-liquid mass ratio of solid / liquid = 1:50; the mass ratio of the added mass of methyl methacrylate and dibenzoyl peroxide to the solid phase in the alcohol solution is methyl methacrylate: dibenzoyl peroxide: solid phase = 3-4:0.1-0.2:1.
[0010] Furthermore, in the step (2), in the acetone solution of benzophenone, the mass percentage of benzophenone is 3% to 4%, and the solvent is acetone; in the aqueous solution of 1-vinyl-2-pyrrolidone, the mass percentage of 1-vinyl-2-pyrrolidone is 16% to 18%, and the solvent is water.
[0011] Furthermore, in the step (2), the solid-liquid mass ratio of the primary modified product dispersed in the acetone solution of benzophenone is primary modified product / acetone solution of benzophenone=1:30; the volume ratio of the aqueous solution of 1-vinyl-2-pyrrolidone added to the volume ratio of the acetone solution of benzophenone used to prepare the dispersion is 1:1.
[0012] Furthermore, in the step (3), the mass percentage of 1-allyl-3-methylimidazole chloride in the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride is 6% to 8%, and the solvent is N,N-dimethylformamide; the solid-liquid mass ratio of the secondary modified product added to the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride is solid / liquid=1:50; the mass ratio of the added mass of the acetic anhydride to the mass of the secondary modified product in the solution to which it is added is acetic anhydride:secondary modified product=2-4:1.
[0013] The present invention also discloses a method for preparing the above-mentioned PVC film layer, comprising weighing each component according to the weight proportion, and then premixing each component in a high-speed mixer for 15 to 20 minutes, transferring the premixed mixture into a mixer for mixing, mixing at a temperature of 120° C. for 6 to 8 minutes, and extruding into a film after mixing to obtain the PVC film layer.
[0014] The beneficial effect of the present invention is that the PVC film prepared by the method of the present invention has high strength and toughness, and excellent mechanical properties, so that the tape using the PVC film as the base layer is not easily damaged or cracked by force, and has a good bonding effect. DETAILED DESCRIPTION
[0015] The present invention will be further described below in conjunction with the embodiments.
[0016] Example 1
[0017] A high-strength and high-tenacity adhesive tape and its preparation process, comprising a PVC film layer and a glue layer, wherein the raw materials of the PVC film layer include PVC, calcium carbonate, modified carbon fiber, magnesium stearate, acetyl tributyl citrate, dioctyl phthalate and titanium dioxide powder, wherein the raw materials are calculated by weight as follows: 100 parts of PVC, 3 parts of calcium carbonate, 20 parts of modified carbon fiber, 5 parts of magnesium stearate, 4 parts of acetyl tributyl citrate, 1 part of dioctyl phthalate, 1 part of titanium dioxide powder, and each solid component is a sieved powder with a mesh size of 500. The modification method of the modified carbon fiber is as follows:
[0018] (1) preparing an ethanol solution of γ-aminopropyl triethoxysilane, wherein the concentration of γ-aminopropyl triethoxysilane in the ethanol solution is 1 g / 100 mL, and the solvent is ethanol; immersing carbon fiber in the ethanol solution of γ-aminopropyl triethoxysilane to form a mixed solution, wherein the solid-liquid mass ratio of the carbon fiber immersed in the ethanol solution of γ-aminopropyl triethoxysilane is carbon fiber / ethanol solution of γ-aminopropyl triethoxysilane=1:80; the mixed solution is kept at a constant temperature of 50±3° C. in a water bath, and after reaching the temperature, glacial acetic acid is added dropwise to adjust the pH of the mixed solution to 4, and then the mixed solution is stirred at a constant temperature of 50±3° C. for 30 minutes, air-cooled to room temperature, solid-liquid separated, the solid phase is washed with ethanol 3 times, dried, and the dried solid phase is immersed again An alcohol solution is formed in ethanol, and the dried solid phase is immersed in ethanol again to form an alcohol solution with a solid-liquid mass ratio of solid / liquid=1:50; the alcohol solution is kept constant temperature at 70±3°C in a water bath, and condensed and refluxed; the alcohol solution is stirred, and methyl methacrylate is added to the alcohol solution during the stirring process. After the addition is completed, the alcohol solution is stirred for 10 minutes, and then dibenzoyl peroxide is added to the alcohol solution under stirring, and the mass ratio of the added mass of methyl methacrylate and dibenzoyl peroxide to the solid phase in the alcohol solution is methyl methacrylate: dibenzoyl peroxide: solid phase=3:0.1:1; after the addition is completed, the alcohol solution is continued to be stirred at a constant temperature of 70±3°C for 5h, and then air-cooled to room temperature, solid-liquid separation, the solid phase is washed with ethanol 3 times, and dried at 60°C to obtain a primary modified product;
[0019] (2) preparing an acetone solution of benzophenone, wherein the mass percentage of benzophenone in the acetone solution of benzophenone is 3%, and the solvent is acetone; preparing an aqueous solution of 1-vinyl-2-pyrrolidone, wherein the mass percentage of 1-vinyl-2-pyrrolidone in the aqueous solution of 1-vinyl-2-pyrrolidone is 16%, and the solvent is water; dispersing the primary modified product in the acetone solution of benzophenone to form a dispersion, wherein the solid-liquid mass ratio of the primary modified product dispersed in the acetone solution of benzophenone is: / benzophenone acetone solution = 1:30; stirring the dispersion, adding the aqueous solution of 1-vinyl-2-pyrrolidone to the dispersion during the stirring process, the volume ratio of the aqueous solution of 1-vinyl-2-pyrrolidone added to the volume of the benzophenone acetone solution used to prepare the dispersion is 1:1; after the addition is completed, stirring the dispersion for 20 minutes, then pouring the dispersion into a glass dish, irradiating with ultraviolet light for 10 minutes, then separating the solid and the liquid, washing the solid phase with ethanol and water twice each, and drying at 60° C. to obtain a secondary modified product;
[0020] (3) preparing an N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride in a reactor in a nitrogen atmosphere, wherein the mass percentage of 1-allyl-3-methylimidazole chloride in the N,N-dimethylformamide solution is 6%, and the solvent is N,N-dimethylformamide; then adding the secondary modified product to the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride under nitrogen protection; adding the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride to the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride; The solid-liquid mass ratio of the secondary modified product added to the amide liquid is solid / liquid=1:50; after the addition is completed, stirring is performed for 10 minutes, and then acetic anhydride is added under stirring, and the added mass ratio of the acetic anhydride to the mass of the secondary modified product in the solution added thereto is acetic anhydride: secondary modified product=2:1; after the addition is completed, stirring is continued for 5 minutes under nitrogen protection, and then the reactor is closed, the water bath is kept at a constant temperature of 60±2°C for 3 hours, and then the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with ethanol 3 times, and dried at 60°C to obtain the modified carbon fiber.
[0021] The preparation method of the above-mentioned PVC film layer is to weigh each component according to the above-mentioned weight proportion, and then premix the components in a high-speed mixer for 15 minutes, transfer the premixed mixture into a mixer for mixing, mix at 120°C for 7 minutes, and extrude into a film after mixing to obtain the above-mentioned PVC film layer.
[0022] Example 2
[0023] A high-strength and high-tenacity adhesive tape and its preparation process, comprising a PVC film layer and an adhesive layer, wherein the raw materials of the PVC film layer include PVC, calcium carbonate, modified carbon fiber, magnesium stearate, acetyl tributyl citrate, dioctyl phthalate and titanium dioxide powder, wherein the raw materials are calculated by weight as follows: 100 parts of PVC, 4 parts of calcium carbonate, 24 parts of modified carbon fiber, 6 parts of magnesium stearate, 6 parts of acetyl tributyl citrate, 2 parts of dioctyl phthalate, 2 parts of titanium dioxide powder, and each solid component is a sieved powder with a mesh size of 500. The modification method of the modified carbon fiber is as follows:
[0024] (1) preparing an ethanol solution of γ-aminopropyl triethoxysilane, wherein the concentration of γ-aminopropyl triethoxysilane in the ethanol solution is 1 g / 100 mL, and the solvent is ethanol; immersing carbon fiber in the ethanol solution of γ-aminopropyl triethoxysilane to form a mixed solution, wherein the solid-liquid mass ratio of the carbon fiber immersed in the ethanol solution of γ-aminopropyl triethoxysilane is carbon fiber / ethanol solution of γ-aminopropyl triethoxysilane=1:80; the mixed solution is kept at a constant temperature of 50±3° C. in a water bath, and after reaching the temperature, glacial acetic acid is added dropwise to adjust the pH of the mixed solution to 4, and then the mixed solution is stirred at a constant temperature of 50±3° C. for 30 minutes, air-cooled to room temperature, solid-liquid separated, the solid phase is washed with ethanol 3 times, dried, and the dried solid phase is immersed again An alcohol solution is formed in ethanol, and the dried solid phase is immersed in ethanol again to form an alcohol solution with a solid-liquid mass ratio of solid / liquid=1:50; the alcohol solution is kept constant temperature at 70±3°C in a water bath, and condensed and refluxed; the alcohol solution is stirred, and methyl methacrylate is added to the alcohol solution during the stirring process. After the addition is completed, the alcohol solution is stirred for 10 minutes, and then dibenzoyl peroxide is added to the alcohol solution under stirring, and the mass ratio of the added mass of methyl methacrylate and dibenzoyl peroxide to the solid phase in the alcohol solution is methyl methacrylate: dibenzoyl peroxide: solid phase=3:0.1:1; after the addition is completed, the alcohol solution is continued to be stirred at a constant temperature of 70±3°C for 5h, and then air-cooled to room temperature, solid-liquid separation, the solid phase is washed with ethanol 3 times, and dried at 60°C to obtain a primary modified product;
[0025] (2) preparing an acetone solution of benzophenone, wherein the mass percentage of benzophenone in the acetone solution of benzophenone is 3%, and the solvent is acetone; preparing an aqueous solution of 1-vinyl-2-pyrrolidone, wherein the mass percentage of 1-vinyl-2-pyrrolidone in the aqueous solution of 1-vinyl-2-pyrrolidone is 16%, and the solvent is water; dispersing the primary modified product in the acetone solution of benzophenone to form a dispersion, wherein the solid-liquid mass ratio of the primary modified product dispersed in the acetone solution of benzophenone is: / benzophenone acetone solution = 1:30; stirring the dispersion, adding the aqueous solution of 1-vinyl-2-pyrrolidone to the dispersion during the stirring process, the volume ratio of the aqueous solution of 1-vinyl-2-pyrrolidone added to the volume of the benzophenone acetone solution used to prepare the dispersion is 1:1; after the addition is completed, stirring the dispersion for 20 minutes, then pouring the dispersion into a glass dish, irradiating with ultraviolet light for 10 minutes, then separating the solid and the liquid, washing the solid phase with ethanol and water twice each, and drying at 60° C. to obtain a secondary modified product;
[0026] (3) preparing an N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride in a reactor in a nitrogen atmosphere, wherein the mass percentage of 1-allyl-3-methylimidazole chloride in the N,N-dimethylformamide solution is 6%, and the solvent is N,N-dimethylformamide; then adding the secondary modified product to the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride under nitrogen protection; adding the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride to the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride; The solid-liquid mass ratio of the secondary modified product added to the amide liquid is solid / liquid=1:50; after the addition is completed, stirring is performed for 10 minutes, and then acetic anhydride is added under stirring, and the added mass ratio of the acetic anhydride to the mass of the secondary modified product in the solution added thereto is acetic anhydride: secondary modified product=3:1; after the addition is completed, stirring is continued for 5 minutes under nitrogen protection, and then the reactor is closed, the water bath is kept at a constant temperature of 60±2°C for 3 hours, and then the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with ethanol 3 times, and dried at 60°C to obtain the modified carbon fiber.
[0027] The preparation method of the above-mentioned PVC film layer is to weigh each component according to the above-mentioned weight proportion, and then premix the components in a high-speed mixer for 15 minutes, transfer the premixed mixture into a mixer for mixing, mix at 120°C for 7 minutes, and extrude into a film after mixing to obtain the above-mentioned PVC film layer.
[0028] Example 3
[0029] A high-strength and high-tenacity adhesive tape and its preparation process, comprising a PVC film layer and an adhesive layer, wherein the raw materials of the PVC film layer include PVC, calcium carbonate, modified carbon fiber, magnesium stearate, acetyl tributyl citrate, dioctyl phthalate and titanium dioxide powder, wherein the raw materials are calculated by weight as follows: 100 parts of PVC, 4 parts of calcium carbonate, 26 parts of modified carbon fiber, 7 parts of magnesium stearate, 8 parts of acetyl tributyl citrate, 3 parts of dioctyl phthalate, 3 parts of titanium dioxide powder, and each solid component is a sieved powder with a mesh size of 500. The modification method of the modified carbon fiber is as follows:
[0030] (1) preparing an ethanol solution of γ-aminopropyl triethoxysilane, wherein the concentration of γ-aminopropyl triethoxysilane in the ethanol solution is 2 g / 100 mL, and the solvent is ethanol; immersing carbon fiber in the ethanol solution of γ-aminopropyl triethoxysilane to form a mixed solution, wherein the solid-liquid mass ratio of the carbon fiber immersed in the ethanol solution of γ-aminopropyl triethoxysilane is carbon fiber / ethanol solution of γ-aminopropyl triethoxysilane=1:80; the mixed solution is kept at a constant temperature of 50±3° C. in a water bath, and after reaching the temperature, glacial acetic acid is added dropwise to adjust the pH of the mixed solution to 4, and then the mixed solution is stirred at a constant temperature of 50±3° C. for 30 min, air-cooled to room temperature, solid-liquid separated, the solid phase is washed with ethanol 3 times, dried, and the dried solid phase is immersed again An alcohol solution is formed in ethanol, and the dried solid phase is immersed in ethanol again to form an alcohol solution with a solid-liquid mass ratio of solid / liquid=1:50; the alcohol solution is kept constant temperature at 70±3°C in a water bath, and condensed and refluxed; the alcohol solution is stirred, and methyl methacrylate is added to the alcohol solution during the stirring process. After the addition is completed, the alcohol solution is stirred for 10 minutes, and then dibenzoyl peroxide is added to the alcohol solution under stirring, and the mass ratio of the added mass of methyl methacrylate and dibenzoyl peroxide to the solid phase in the alcohol solution is methyl methacrylate: dibenzoyl peroxide: solid phase=4:0.2:1; after the addition is completed, the alcohol solution is continued to be stirred at a constant temperature of 70±3°C for 5h, and then air-cooled to room temperature, solid-liquid separation, the solid phase is washed with ethanol 3 times, and dried at 60°C to obtain a primary modified product;
[0031] (2) preparing an acetone solution of benzophenone, wherein the mass percentage of benzophenone in the acetone solution of benzophenone is 4%, and the solvent is acetone; preparing an aqueous solution of 1-vinyl-2-pyrrolidone, wherein the mass percentage of 1-vinyl-2-pyrrolidone in the aqueous solution of 1-vinyl-2-pyrrolidone is 18%, and the solvent is water; dispersing the primary modified product in the acetone solution of benzophenone to form a dispersion, wherein the solid-liquid mass ratio of the primary modified product dispersed in the acetone solution of benzophenone is: / benzophenone acetone solution = 1:30; stirring the dispersion, adding the aqueous solution of 1-vinyl-2-pyrrolidone to the dispersion during the stirring process, the volume ratio of the aqueous solution of 1-vinyl-2-pyrrolidone added to the volume of the benzophenone acetone solution used to prepare the dispersion is 1:1; after the addition is completed, stirring the dispersion for 20 minutes, then pouring the dispersion into a glass dish, irradiating with ultraviolet light for 10 minutes, then separating the solid and the liquid, washing the solid phase with ethanol and water twice each, and drying at 60° C. to obtain a secondary modified product;
[0032] (3) preparing an N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride in a reactor in a nitrogen atmosphere, wherein the mass percentage of 1-allyl-3-methylimidazole chloride in the N,N-dimethylformamide solution is 8%, and the solvent is N,N-dimethylformamide; then adding the secondary modified product to the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride under nitrogen protection; adding the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride to the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride; The solid-liquid mass ratio of the secondary modified product added to the amide liquid is solid / liquid=1:50; after the addition is completed, stirring is performed for 10 minutes, and then acetic anhydride is added under stirring, and the added mass ratio of the acetic anhydride to the mass of the secondary modified product in the solution added thereto is acetic anhydride: secondary modified product=3:1; after the addition is completed, stirring is continued for 5 minutes under nitrogen protection, and then the reactor is closed, the water bath is kept at a constant temperature of 60±2°C for 3 hours, and then the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with ethanol 3 times, and dried at 60°C to obtain the modified carbon fiber.
[0033] The preparation method of the above-mentioned PVC film layer is to weigh each component according to the above-mentioned weight proportion, and then premix the components in a high-speed mixer for 15 minutes, transfer the premixed mixture into a mixer for mixing, mix at 120°C for 7 minutes, and extrude into a film after mixing to obtain the above-mentioned PVC film layer.
[0034] Example 4
[0035] A high-strength and high-tenacity adhesive tape and its preparation process, comprising a PVC film layer and an adhesive layer, wherein the raw materials of the PVC film layer include PVC, calcium carbonate, modified carbon fiber, magnesium stearate, tributyl acetyl citrate, dioctyl phthalate and titanium dioxide powder, wherein the raw materials are calculated by weight as follows: 100 parts of PVC, 5 parts of calcium carbonate, 30 parts of modified carbon fiber, 8 parts of magnesium stearate, 10 parts of tributyl acetyl citrate, 4 parts of dioctyl phthalate, 4 parts of titanium dioxide powder, and each solid component is a sieved powder with a mesh size of 500. The modification method of the modified carbon fiber is as follows:
[0036] (1) preparing an ethanol solution of γ-aminopropyl triethoxysilane, wherein the concentration of γ-aminopropyl triethoxysilane in the ethanol solution is 2 g / 100 mL, and the solvent is ethanol; immersing carbon fiber in the ethanol solution of γ-aminopropyl triethoxysilane to form a mixed solution, wherein the solid-liquid mass ratio of the carbon fiber immersed in the ethanol solution of γ-aminopropyl triethoxysilane is carbon fiber / ethanol solution of γ-aminopropyl triethoxysilane=1:80; the mixed solution is kept at a constant temperature of 50±3° C. in a water bath, and after reaching the temperature, glacial acetic acid is added dropwise to adjust the pH of the mixed solution to 4, and then the mixed solution is stirred at a constant temperature of 50±3° C. for 30 min, air-cooled to room temperature, solid-liquid separated, the solid phase is washed with ethanol 3 times, dried, and the dried solid phase is immersed again An alcohol solution is formed in ethanol, and the dried solid phase is immersed in ethanol again to form an alcohol solution with a solid-liquid mass ratio of solid / liquid=1:50; the alcohol solution is kept constant temperature at 70±3°C in a water bath, and condensed and refluxed; the alcohol solution is stirred, and methyl methacrylate is added to the alcohol solution during the stirring process. After the addition is completed, the alcohol solution is stirred for 10 minutes, and then dibenzoyl peroxide is added to the alcohol solution under stirring, and the mass ratio of the added mass of methyl methacrylate and dibenzoyl peroxide to the solid phase in the alcohol solution is methyl methacrylate: dibenzoyl peroxide: solid phase=4:0.2:1; after the addition is completed, the alcohol solution is continued to be stirred at a constant temperature of 70±3°C for 5h, and then air-cooled to room temperature, solid-liquid separation, the solid phase is washed with ethanol 3 times, and dried at 60°C to obtain a primary modified product;
[0037] (2) preparing an acetone solution of benzophenone, wherein the mass percentage of benzophenone in the acetone solution of benzophenone is 4%, and the solvent is acetone; preparing an aqueous solution of 1-vinyl-2-pyrrolidone, wherein the mass percentage of 1-vinyl-2-pyrrolidone in the aqueous solution of 1-vinyl-2-pyrrolidone is 18%, and the solvent is water; dispersing the primary modified product in the acetone solution of benzophenone to form a dispersion, wherein the solid-liquid mass ratio of the primary modified product dispersed in the acetone solution of benzophenone is: / benzophenone acetone solution = 1:30; stirring the dispersion, adding the aqueous solution of 1-vinyl-2-pyrrolidone to the dispersion during the stirring process, the volume ratio of the aqueous solution of 1-vinyl-2-pyrrolidone added to the volume of the benzophenone acetone solution used to prepare the dispersion is 1:1; after the addition is completed, stirring the dispersion for 20 minutes, then pouring the dispersion into a glass dish, irradiating with ultraviolet light for 10 minutes, then separating the solid and the liquid, washing the solid phase with ethanol and water twice each, and drying at 60° C. to obtain a secondary modified product;
[0038] (3) preparing an N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride in a reactor in a nitrogen atmosphere, wherein the mass percentage of 1-allyl-3-methylimidazole chloride in the N,N-dimethylformamide solution is 8%, and the solvent is N,N-dimethylformamide; then adding the secondary modified product to the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride under nitrogen protection; adding the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride to the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride; The solid-liquid mass ratio of the secondary modified product added to the amide liquid is solid / liquid=1:50; after the addition is completed, stirring is performed for 10 minutes, and then acetic anhydride is added under stirring, and the added mass ratio of the acetic anhydride to the mass of the secondary modified product in the solution added thereto is acetic anhydride: secondary modified product=4:1; after the addition is completed, stirring is continued for 5 minutes under nitrogen protection, and then the reactor is closed, the water bath is kept at a constant temperature of 60±2°C for 3 hours, and then the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with ethanol 3 times, and dried at 60°C to obtain the modified carbon fiber.
[0039] The preparation method of the above-mentioned PVC film layer is to weigh each component according to the above-mentioned weight proportion, and then premix the components in a high-speed mixer for 15 minutes, transfer the premixed mixture into a mixer for mixing, mix at 120°C for 7 minutes, and extrude into a film after mixing to obtain the above-mentioned PVC film layer.
[0040] Comparative Example 1
[0041] A PVC film layer for comparison, the raw materials of the PVC film layer include PVC, calcium carbonate, carbon fiber, magnesium stearate, acetyl tributyl citrate, dioctyl phthalate and titanium dioxide powder, the raw materials are calculated by weight as follows: 100 parts of PVC, 4 parts of calcium carbonate, 26 parts of carbon fiber, 7 parts of magnesium stearate, 8 parts of acetyl tributyl citrate, 3 parts of dioctyl phthalate, 3 parts of titanium dioxide powder, and each solid component is a sieved powder passing through 500 mesh.
[0042] The preparation method of the above-mentioned PVC film layer is to weigh each component according to the above-mentioned weight proportion, and then premix the components in a high-speed mixer for 15 minutes, transfer the premixed mixture into a mixer for mixing, mix at 120°C for 7 minutes, and extrude into a film after mixing to obtain the above-mentioned PVC film layer.
[0043] Comparative Example 2
[0044] A PVC film layer for comparison, the raw materials of the PVC film layer include PVC, calcium carbonate, modified carbon fiber, magnesium stearate, acetyl tributyl citrate, dioctyl phthalate and titanium dioxide powder, and the raw materials are calculated by weight as follows: 100 parts of PVC, 4 parts of calcium carbonate, 26 parts of modified carbon fiber, 7 parts of magnesium stearate, 8 parts of acetyl tributyl citrate, 3 parts of dioctyl phthalate, 3 parts of titanium dioxide powder, and each solid component is a sieved powder passing through 500 mesh. The modification method of the modified carbon fiber is as follows: preparing an ethanol solution of γ-aminopropyl triethoxysilane, wherein the concentration of γ-aminopropyl triethoxysilane in the ethanol solution of γ-aminopropyl triethoxysilane is 2g / 100mL, and the solvent is ethanol; immersing the carbon fiber in the ethanol solution of γ-aminopropyl triethoxysilane to form a mixed liquid, wherein the solid-liquid mass ratio of the carbon fiber immersed in the ethanol solution of γ-aminopropyl triethoxysilane is carbon fiber / γ-aminopropyl triethoxysilane ethanol solution=1:80; the mixed liquid is kept at a constant temperature of 50±3°C in a water bath, and after reaching the temperature, glacial acetic acid is added dropwise to adjust the pH of the mixed liquid to 4, and then the mixed liquid is stirred at a constant temperature of 50±3°C for 30min, air-cooled to room temperature, solid-liquid separated, the solid phase is washed 3 times with ethanol, and dried. The alcohol solution was immersed in ethanol again to form an alcohol solution, and the solid phase after drying was immersed in ethanol again to form an alcohol solution with a solid-liquid mass ratio of solid / liquid = 1:50; the alcohol solution was kept at a constant temperature of 70±3°C in a water bath, and condensed and refluxed; the alcohol solution was stirred, and methyl methacrylate was added to the alcohol solution during the stirring process. After the addition was completed, the alcohol solution was stirred for 10 minutes, and then dibenzoyl peroxide was added to the alcohol solution under stirring, and the mass ratio of the added mass of methyl methacrylate and dibenzoyl peroxide to the solid phase in the alcohol solution was methyl methacrylate: dibenzoyl peroxide: solid phase = 4:0.2:1; after the addition was completed, the alcohol solution was continued to be stirred at a constant temperature of 70±3°C for 5h, and then air-cooled to room temperature, solid-liquid separation, the solid phase was washed 3 times with ethanol, and dried at 60°C to obtain the modified carbon fiber described in this comparative example.
[0045] The preparation method of the above-mentioned PVC film layer is to weigh each component according to the above-mentioned weight proportion, and then premix the components in a high-speed mixer for 15 minutes, transfer the premixed mixture into a mixer for mixing, mix at 120°C for 7 minutes, and extrude into a film after mixing to obtain the above-mentioned PVC film layer.
[0046] Comparative Example 3
[0047] A PVC film layer for comparison, the raw materials of the PVC film layer include PVC, calcium carbonate, modified carbon fiber, magnesium stearate, acetyl tributyl citrate, dioctyl phthalate and titanium dioxide powder, and the raw materials are calculated by weight as follows: 100 parts of PVC, 4 parts of calcium carbonate, 26 parts of modified carbon fiber, 7 parts of magnesium stearate, 8 parts of acetyl tributyl citrate, 3 parts of dioctyl phthalate, 3 parts of titanium dioxide powder, and each solid component is a sieved powder passing through 500 mesh. The modification method of the modified carbon fiber is as follows: preparing an acetone solution of benzophenone, wherein the mass percentage of benzophenone in the acetone solution of benzophenone is 4%, and the solvent is acetone; preparing an aqueous solution of 1-vinyl-2-pyrrolidone; wherein the mass percentage of 1-vinyl-2-pyrrolidone in the aqueous solution of 1-vinyl-2-pyrrolidone is 18%, and the solvent is water; dispersing carbon fiber in the acetone solution of benzophenone to form a dispersion, wherein the solid-liquid mass ratio of the carbon fiber dispersed in the acetone solution of benzophenone is carbon fiber / benzophenone. The acetone solution of benzophenone = 1:30; stirring the dispersion, adding the aqueous solution of 1-vinyl-2-pyrrolidone to the dispersion during the stirring process, the volume ratio of the aqueous solution of 1-vinyl-2-pyrrolidone added to the volume of the acetone solution of benzophenone used to prepare the dispersion is 1:1; after the addition is completed, the dispersion is stirred for 20 minutes, and then the dispersion is poured into a glass dish, irradiated with ultraviolet light for 10 minutes, and then solid-liquid separation is performed, the solid phase is washed twice with ethanol and water respectively, and dried at 60°C to obtain the modified carbon fiber described in this comparative example.
[0048] The preparation method of the above-mentioned PVC film layer is to weigh each component according to the above-mentioned weight proportion, and then premix the components in a high-speed mixer for 15 minutes, transfer the premixed mixture into a mixer for mixing, mix at 120°C for 7 minutes, and extrude into a film after mixing to obtain the above-mentioned PVC film layer.
[0049] Comparative Example 4
[0050] A PVC film layer for comparison, the raw materials of the PVC film layer include PVC, calcium carbonate, modified carbon fiber, magnesium stearate, acetyl tributyl citrate, dioctyl phthalate and titanium dioxide powder, and the raw materials are calculated by weight as follows: 100 parts of PVC, 4 parts of calcium carbonate, 26 parts of modified carbon fiber, 7 parts of magnesium stearate, 8 parts of acetyl tributyl citrate, 3 parts of dioctyl phthalate, 3 parts of titanium dioxide powder, and each solid component is a sieved powder passing through 500 mesh. The modification method of the modified carbon fiber is as follows: preparing N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride in a reactor in a nitrogen atmosphere, wherein the mass percentage of 1-allyl-3-methylimidazole chloride in the N,N-dimethylformamide solution is 8%, and the solvent is N,N-dimethylformamide; then adding carbon fiber to the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride under nitrogen protection; adding carbon fiber to the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride; The solid-liquid mass ratio of carbon fiber added to the N,N-dimethylformamide solution is solid / liquid = 1:50; after the addition is completed, the mixture is stirred for 10 minutes, and then acetic anhydride is added under stirring, and the mass ratio of the added mass of the acetic anhydride to the mass of the carbon fiber in the solution added thereto is acetic anhydride: carbon fiber = 3:1; after the addition is completed, the mixture is stirred for 5 minutes under nitrogen protection, and then the reactor is closed, and the temperature is kept constant at 60±2°C in a water bath for 3 hours, and then the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with ethanol 3 times, and dried at 60°C to obtain the modified carbon fiber described in this comparative example.
[0051] The preparation method of the above-mentioned PVC film layer is to weigh each component according to the above-mentioned weight proportion, and then premix the components in a high-speed mixer for 15 minutes, transfer the premixed mixture into a mixer for mixing, mix at 120°C for 7 minutes, and extrude into a film after mixing to obtain the above-mentioned PVC film layer.
[0052] Example 5
[0053] The tensile strength and elongation of the PVC film layer prepared by the methods described in the above embodiments and comparative examples were tested according to the requirements of standard GB / T1040-2018. The sizes of the test specimens were all standard 1A type, and the tensile speed was set to 10 mm / min. The results are shown in Table 1.
[0054] Table 1
[0055] Experimental Group Tensile strength / MPa Elongation / % Example 1 30.25 370 Example 2 31.91 379 Example 3 33.62 386 Example 4 32.87 382 Comparative Example 1 19.30 257 Comparative Example 2 23.66 274 Comparative Example 3 22.19 293 Comparative Example 4 23.07 308
[0056] As shown in Table 1, the PVC film prepared by the method of the present invention has high strength and toughness, and excellent mechanical properties. This is mainly due to the fact that carbon fiber has a significant promoting effect on the mechanical properties of PVC, but when unmodified or insufficiently modified carbon fiber is directly added to PVC, due to the agglomeration of the carbon fiber itself and the poor bonding between the carbon fiber and the PVC phase, the carbon fiber distribution is uneven, resulting in insufficient local strength of the film. During the stretching process, these weak areas are prone to cracks and expand first, resulting in low overall strength and toughness of the material. In addition, due to poor wettability and bonding between the two junctions, the two phases are prone to peeling off and forming cracks, which has an adverse effect on the improvement of material strength.
[0057] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A high-strength and high-toughness adhesive tape, characterized in that: The invention comprises a PVC film layer and a glue layer, wherein the raw materials of the PVC film layer comprise PVC, calcium carbonate, modified carbon fiber, magnesium stearate, acetyl tributyl citrate, dioctyl phthalate and titanium dioxide powder, wherein the raw materials are calculated by weight as follows: 100 parts of PVC, 3-5 parts of calcium carbonate, 20-30 parts of modified carbon fiber, 5-8 parts of magnesium stearate, 4-10 parts of acetyl tributyl citrate, 1-4 parts of dioctyl phthalate, 1-4 parts of titanium dioxide powder, and each solid component is a sieved powder with a mesh size of 500. The modification method of the modified carbon fiber is as follows: (1) preparing an ethanol solution of γ-aminopropyltriethoxysilane, immersing the carbon fiber in the ethanol solution of γ-aminopropyltriethoxysilane to form a mixed solution, the mixed solution is kept at a constant temperature of 50±3°C in a water bath, glacial acetic acid is added dropwise to adjust the pH of the mixed solution to 4-5, then the mixed solution is stirred at a constant temperature of 50±3°C for 30-50min, air-cooled to room temperature, solid-liquid separated, the solid phase is washed with ethanol for more than 3 times, dried, and the dried solid phase is immersed in ethanol again to form an alcohol solution, the alcohol solution is kept at a constant temperature of 70±3°C in a water bath, condensed and refluxed; stirring the alcohol solution, adding methyl methacrylate to the alcohol solution during the stirring process, stirring the alcohol solution for more than 10min after the addition is completed, and then adding dibenzoyl peroxide to the alcohol solution under stirring, continuing to stir the alcohol solution at a constant temperature of 70±3°C for more than 5h after the addition is completed, then air-cooled to room temperature, solid-liquid separated, the solid phase is washed with ethanol for more than 3 times, and dried at 60°C to obtain a primary modified product; (2) preparing an acetone solution of benzophenone and an aqueous solution of 1-vinyl-2-pyrrolidone; dispersing the primary modified product in the acetone solution of benzophenone to form a dispersion, stirring the dispersion, adding the aqueous solution of 1-vinyl-2-pyrrolidone to the dispersion during the stirring process, stirring the dispersion for more than 20 minutes after the addition is completed, then pouring the dispersion into a glass dish, irradiating with an ultraviolet lamp for 10 to 15 minutes, then separating the solid and the liquid, washing the solid phase with ethanol and water twice each, and drying at 60° C. to obtain a secondary modified product; (3) A N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride is prepared in a reactor in a nitrogen atmosphere, and then the secondary modified product is added to the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride under nitrogen protection; after the addition is completed, the mixture is stirred for more than 10 minutes, and then acetic anhydride is added under stirring. After the addition is completed, the mixture is stirred for more than 5 minutes under nitrogen protection, and then the reactor is closed, and the temperature is kept constant at 60±2° C. in a water bath for more than 3 hours, and then the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with ethanol for more than 3 times, and then dried at 60° C. to obtain the modified carbon fiber.
2. A high-strength and high-tenacity adhesive tape according to claim 1, characterized in that: In the step (1), the concentration of γ-aminopropyltriethoxysilane in the ethanol solution of γ-aminopropyltriethoxysilane is 1 to 2 g / 100 mL, and the solvent is ethanol; the solid-liquid mass ratio of the carbon fiber immersed in the ethanol solution of γ-aminopropyltriethoxysilane is carbon fiber / ethanol solution of γ-aminopropyltriethoxysilane=1:
80.
3. A high-strength and high-tenacity adhesive tape according to claim 1, characterized in that: In the step (1), the dried solid phase is immersed in ethanol again to form an alcohol solution with a solid-liquid mass ratio of solid / liquid = 1:50; the mass ratio of the added mass of methyl methacrylate and dibenzoyl peroxide to the solid phase in the alcohol solution is methyl methacrylate: dibenzoyl peroxide: solid phase = 3-4:0.1-0.2:
1.
4. The high-strength and high-tenacity adhesive tape according to claim 1, characterized in that: In the step (2), in the acetone solution of benzophenone, the mass percentage of benzophenone is 3% to 4%, and the solvent is acetone; in the aqueous solution of 1-vinyl-2-pyrrolidone, the mass percentage of 1-vinyl-2-pyrrolidone is 16% to 18%, and the solvent is water.
5. The high-strength and high-tenacity adhesive tape according to claim 1, characterized in that: In the step (2), the solid-liquid mass ratio of the primary modified product dispersed in the acetone solution of benzophenone is primary modified product / acetone solution of benzophenone=1:30; the volume ratio of the aqueous solution of 1-vinyl-2-pyrrolidone added to the volume ratio of the acetone solution of benzophenone used to prepare the dispersion is 1:
1.
6. The high-strength and high-tenacity adhesive tape according to claim 1, characterized in that: In the step (3), the mass percentage of 1-allyl-3-methylimidazole chloride in the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride is 6% to 8%, and the solvent is N,N-dimethylformamide; the solid-liquid mass ratio of the secondary modified product added to the N,N-dimethylformamide solution of 1-allyl-3-methylimidazole chloride is solid / liquid=1:50; the mass ratio of the added mass of the acetic anhydride to the mass of the secondary modified product in the solution to which it is added is acetic anhydride:secondary modified product=2-4:1.
